New initiatives with fludarabine monophosphate in hematologic malignancies - Keating, M.J.; O'Brien, S.; Robertson, L.E.; Kantarjian, H.; Dimopoulos, M.; McLaughlin, P.; Cabanillas, F.; Gregoire, V.; Yang, L.-Y.; Gandhi, V.; Estey, E.; Plunkett, W. (Seminars in Oncology, 1993)
Fludarabine monophosphate (fludarabine) was initially discovered to have significant activity in indolent lymphoma and chronic lymphocytic leukemia (CLL). The major clinical experience with fludarabine is in previously treated patients with CLL. In such patients the complete and partial response rate (CR + PR) is over 50%. These results were obtained with 5-day schedules of fludarabine 25 to 30 mg/m2/d. Subsequent schedules have explored once-a- week fludarabine and a 3-day schedule every 4 weeks. These strategies, in particular the once-a-week schedule, have obtained inferior results. The addition of prednisone has not been associated with an improvement in response rate or survival. The application of fludarabine to previously untreated patients demonstrated a CR + PR rate of 75% to 80%. The addition of prednisone did not improve the response rate or survival in this group of patients. A significant concern in patients with CLL treated with fludarabine is a decrease in the CD4 and CD8 counts. Despite median posttreatment counts of approximately 200 CD4 lymphocytes/μL, the incidence of infections in patients in remission off therapy is low. Major clinical activity has been demonstrated with fludarabine in Waldenstrom's macroglobulinemia, in which more than one third of refractory patients achieve a CR or PR. Responding patients with anemia or thrombocytopenia have a marked improvement in blood counts. The duration of response has been long (>30 months) in most responders. The early activity of fludarabine as a single agent in phase I/II studies in indolent lymphoma subsequently has been confirmed by a number of investigators. Fifty percent to 60% of patients with follicular lymphomas respond to fludarabine as a single agent. A number of these responses are complete despite the patients having received extensive prior treatment. A number of combination programs are being developed in CLL and indolent lymphoma. The combination of fludarabine with doxorubicin and prednisone has been developed and is being studied in phase I/II clinical trials. In addition, combinations of fludarabine and cytarabine with or without cisplatin based on elegant preclinical pharmacokinetic rationales have been applied to CLL with impressive cytoreductive activity but significant myelosuppression. A new combination of fludarabine, mitoxantrone, and dexamethasone has been developed for use in lymphoma. Phase I studies demonstrated a high response rate, especially in follicular lymphomas, with a number of patients achieving complete remission. Subsequent phase II studies demonstrate a response rate of 89% in patients with indolent lymphoma. The enhancement of the formation of the triphosphate form of cytarabine in acute myelogenous leukemia blast cells has led to the study of fludarabine and cytarabine in previously treated patients with acute leukemia. The promising results in these patients have led to the application of the fludarabine and cytarabine combination in frontline patients with poor-risk disease and, subsequently, in those with better-risk disease. Results equivalent or superior to traditional combinations have been obtained. The same regimen has been applied to myelodysplastic syndrome patients with a response rate of over 50%. The addition of granulocyte colony-stimulating factor to fludarabine and cytarabine to enhance the cytotoxicity of cytarabine on acute myelogenous leukemia and myelodysplastic syndrome has further improved the response rate. These drugs have now been combined with Idarubicin (Adria Laboratories, Columbus, OH). Fludarabine has been demonstrated to have a marked impact on the inhibition of repair of DNA damage subsequent to radiation and exposure to cytotoxic substances such as cisplatin. These biologic effects have been used to develop clinical protocols exploring the combinations of fludarabine/cisplatin with or without cytarabine and fludarabine/radiation therapy. The expanding use of fludarabine in hematologic malignancies is related to its wide range of biochemical actions. Further use in combinations is anticipated.